A Study on Effect of Nasal Obstruction on Pulmonary Function Tests in Patients with Allergic Nasal Polyposis Attending Medical College Headquarter’s Hospital - Kumar, Kukkapalli Prathap; Sindhuja, Nagisetty; Arshad, Dudekula; Sindhu, B.S. (Journal of Neonatal Surgery, 2025)
Both the upper and lower airways form a contiguous and functionally related organ. Nose performs important functions such as respiration, filtration, humidification and olfaction.[1]Nasal polyposis, is one of the common cause for nasal obstruction. Due to obstruction particles enters the lower airway through oral breathing and causes bronchoconstriction and lower airway irritation.[2] Hence, there seems a relation between upper and lower airways.[3] Aim of the study is to evaluate the impact of nasal obstruction on pulmonary function in patients with allergic nasal polyposis by comparing pulmonary function test (PFT) results before and after surgical intervention. Materials and Methods: This study was conducted on patients aged 20 to 45 years who attended the Department of ENT at Medical College Hospital. A total of 86 patients diagnosed with nasal polyposis were included. All participant underwent surgical intervention and pulmonary function tests (PFTs) were performed at three intervals: preoperatively, and 1 and 3 month postoperatively and results were analyzed and compared. Results: The majority of patients affected by allergic nasal polyposis belonged to the age group around 30 years. The mean age of the study population was 31.09 years. All patients (100%) underwent functional endoscopic sinus surgery. Postoperative evaluation revealed clinically and statistically significant improvements in forced expiratory volume in one second (FEV1) and forced vital capacity (FVC) irrespective of age, gender, or the duration of nasal obstruction. Conclusion: Patients with bilateral nasal obstruction with decreased pulmonary function had significant improvement in pulmonary function after nasal surgery.